Deformation processes during the last stages of the continental collision: the brittle-ductile fault systems in the Bergell and Insubric areas (Eastern Central Alps, Switzerland-Italy) - Ciancaleoni, Laurent (My University, 2005)
The brittle and brittle-ductile fault and shear zone patterns are investigated in the Oligo-Miocene intrusions of the Bergell and Insubric regions in the Eastern Central Alps. In the study area, the late deformation pattern encompasses, from the regional scale up to the microtectonic scale, normal, oblique-slip and strike-slip faults. Much lesser reverse faults occur only at the microtectonic scale. The tectonic regime associated with these faults is distributed in space and time into extensional and transcurrent displacements. Fault data from 120 measurements stations, which altogether represent ca. 3500 fault planes, have been collected in this study. The fault-slip data analysis of the minor fault populations is coherent for both the extensive and strike-slip tectonic regimes and yields a very consistent ENE-WSW directed orientation of the extension axis, i.e. parallel to the Alpine belt direction. Widespread normal faulting is a major event which led to orogen-parallel extension. This extension is materialized by a dominant set of NW-SE striking (transversal) normal faults. A minor part of this extensional deformation is also accommodated by oblique-normal slip on sets of E-W striking (longitudinal) faults. Amongst the former ones, the Forcola fault is a major late Alpine normal fault located at the contact between the middle and upper Penninic units. The brittle-ductile fault consists of mylonites and cataclasites accommodating early Miocene NE-SW extension at the eastern border of the Lepontine dome. This E-dipping extensional structure is a prominent regional structure that: (1) relatively displaces the wall rocks by a significant vertical minimum amount of approximately 3000m. The fault is proposed to be a conjugate fault with respect to the extensional Simplon fault system in the western Central Alps. (2) promoted the space available for emplacement of the 25 Ma old Novate leucogranite. The extensional deformation within the syn-tectonic intrusion is heterogeneous and characterized by conjugated shear zones surrounding lens-shaped domains of weakly deformed granite. These structures developed during fast cooling of the intrusion. This first evidence for orogen-parallel syn-extensional leucogranite emplacement during Oligocene convergence in the Alps brings new insights into the lower timing activity of the Forcola fault. Conversely, new zircon and apatite fission track ages across the Forcola fault give an upper age limit (Langhian) for the cessation of significant vertical movement on the fault. Regarding the Tonale fault, the available fission track data suggest the likelihood of vertical displacements and block rotation along the fault from the Middle Miocene onwards. The strike-slip shearing event commonly but non systematically over imposed on the earlier extensional structures. The transcurrent paleostress field is calculated from conjugated sets of strike-slip faults that define triangular wedges associated with an orogen-parallel orientation of the extension axis. The transcurrent displacements are materialized by: (1) right-lateral slip along reactivated and/or neoformed longitudinal faults and reactivated transversal faults (2) left-lateral slip along N-S to NE-SW oriented faults. On the basis of these observations, the following Neogene tectonic evolution of the Alpine collision belt in the Eastern Central Alps is proposed. In response to the northwestward motion and anticlockwise rotation of the Apulian microplate, the internal domain of the belt in the Bergell region reacted by E-directed lateral extrusion by the late Oligocene onwards. This lateral escape was typically accommodated by a combination of normal and transcurrent displacements. The onset of orogen-parallel extension at the Forcola fault is kinematically and temporally compatible with the late Oligocene dextral slip at the E-W oriented Tonale Line and sinistral strike-slip at the NE-SW oriented Engadine Line. These prominent shear zones define a regional first order tectonic block that accommodated the E-directed extrusion of the Bergell area. Within the extruding block, the tectonic regime evolved from a major extensive to transtensive tectonic regime to a more transcurrent one. Because of strong lateral confinement due to indentation along the Giudicarie-Pustertal indenter at the end of the Burdigalian, orogen-parallel extension and lateral escape loosed efficiency. With on-going convergence, lateral extrusion was then primarily relocated sideways in the Western and Eastern Alps by the early Miocene onwards, according to free boundary availabilities.
Thèse de doctorat : Université de Neuchâtel, 2005 ; 1897
Keywords: Alpes Centrales orientales; intrusion du Bergell; système de failles Périadriatique; faille, zone de cisaillement; fragile-ductile; granite de Novate; extension; décrochement; extrusion; paléocontrainte; analyse cinématique; traces de fission; exhumation; Néogène; Eastern Central Alps; Bergell intrusion; Periadriatic Fault System; fault, shear zone; brittle-ductile; Novate granite; extension; strike-slip; extrusion; paleostress; kinematic analysis; fission track; exhumation; Neogene